ANALYSIS OF FACTORS INFLUENCING MILKFISH (Chanos -chanos) TAMB PRODUCTION IN LANGSA CITY, ACEH PROVINCE - Ria Tri Anjarsari; Zulkarnain Lubis; Syahbudin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research aims to determine the factors that influence milkfish pond production and determine the production model/strategy of milkfish pond businesses in Cinta Raja Village, East Langsa District, Alue Dua Village, Langsa Baro District, and Seuriget Village, West Langsa District, Langsa City . This research was conducted from December 2023 – February 2024. This research is quantitative descriptive research. Primary data was collected through two types of collection techniques, in the form of observation and interviews by filling in questionnaires. Meanwhile, secondary data in this research was obtained by downloading data from the websites of the relevant agencies and the central statistical agency, as well as from previous research. The sampling technique uses a multistage random sampling technique. In this research, what is thought to influence the production income of traditionally cultivated milkfish ponds is land area, experience, seeds, fertilizer, feed, labor and capital. The results of the research show that the factors that have a real influence on the production of traditional milkfish farming businesses in Langsa City include: land area and seeds, fertilizer, feed and capital. Land area and capital have a negative effect on income, while seeds, fertilizer and feed have a positive effect on income.